Academic freedoms and dignity: The curious case of John Finnis' phobism - Hasanbegović Jasminka (Anali Pravnog Fakulteta u Beogradu)
This paper focuses - through the lens of the Finnis case - on the search for answers to the questions: Where do the boundaries of academic freedom and free speech lie? Did Finnis overstep them with his "extremely discriminatory views against many groups of disadvantaged people" presented in his papers between 1992 and 2011, as it is said in the Petition to stop John Finnis teaching at Oxford University because of his discrimination? Are Finnis' views phobic? The main theses presented in the paper are: The boundaries of academic freedom and freedom of speech have not been overstepped, but these freedoms were abused. Some of these views, as abstractly expressed opinions, are phobic, but there is no tangible proof of any discriminatory behaviour by Finnis towards anybody.